2021
DOI: 10.1101/2021.04.28.441155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Floral scents of a deceptive plant are hyperdiverse and under population-specific phenotypic selection

Abstract: Floral scent is a key mediator in plant-pollinator interactions; however, little is known to what extent intraspecific scent variation is shaped by phenotypic selection, with no information yet in deceptive plants. We recorded 291 scent compounds in deceptive moth fly-pollinated Arum maculatum from various populations north vs. south of the Alps, the highest number so far reported in a single plant species. Scent and fruit set differed between regions, and some, but not all differences in scent could be explai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
(278 reference statements)
0
2
0
Order By: Relevance
“…indole, p-cresol and 2-heptanone) were not correlated with species-specific pollinator attraction. A recent study by Gfrerer et al (2021) also found that variation in the aforementioned foetid-smelling VOCs were not among those which significantly influenced fruit sets in A. maculatum. Given that blends of indole, p-cresol and 2-heptanone are known to be attractive to Psychoda species (Kite et al 1998), these compounds appear to be generally attractive to all species.…”
Section: The Influence Of Spatially Variable Pollinators On a Maculatum Floral Odourmentioning
confidence: 84%
See 1 more Smart Citation
“…indole, p-cresol and 2-heptanone) were not correlated with species-specific pollinator attraction. A recent study by Gfrerer et al (2021) also found that variation in the aforementioned foetid-smelling VOCs were not among those which significantly influenced fruit sets in A. maculatum. Given that blends of indole, p-cresol and 2-heptanone are known to be attractive to Psychoda species (Kite et al 1998), these compounds appear to be generally attractive to all species.…”
Section: The Influence Of Spatially Variable Pollinators On a Maculatum Floral Odourmentioning
confidence: 84%
“…Arum maculatum inflorescences (Fig. 1) are pollinated deceptively, by emitting complex VOC blends which are known to vary within and among populations in England (Kite 1995, Kite et al 1998, Diaz and Kite 2002, France (Chartier et al 2011(Chartier et al , 2013 and across the Alps (Gfrerer et al 2021). The floral odour of A. maculatum is similar to dung or decomposing organic matter (Lack and Diaz 1991), mimicking the natural brood sites of their main pollinators, the moth flies Psychoda phalaenoides and Psycha grisescens (Diptera: Psychodidae).…”
Section: Introductionmentioning
confidence: 99%